Fostering Critical Thinking Skills Through Innovative Elementary School Science Learning - Ongke Ageng Pamorti; Winarno Winarno; Kartika Chrysti Suryandari (Universitas Sebelas Maret, 2024)
Contemporary educational frameworks evolve to prepare learners for real-world challenges, so learners are required to have skills and be able to compete in the 21st century era. Critical thinking skills are high-level thinking skills that are very important for learners to have starting from elementary school, but in fact, critical thinking skills in elementary schools are low. The focus of this research is to describe critical thinking skills through innovation in elementary school science learning. This research uses a literature study research method. Data collection is sourced from relevant articles, journals, and books. Research data analysis through four stages 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusion drawing. The results of this study reveal that learning innovation has an important role because it is able to foster critical thinking skills through HOTS questions, appropriate learning models, and media that can foster critical thinking in students. Some things that need to be considered are the utilization of technology that is developing using technology-based media and the use of HOTS questions and learning models is also considered. So it can be concluded that fostering critical thinking skills through learning innovation can be done through HOTS questions, appropriate learning models, and learning media in elementary school science learning.